Comparison of putative BH3 mimetics AT-101, HA14-1, sabutoclax and TW-37 with ABT-737 in platelets. (2nd January 2021) - Wei, Hao; Harper, Matthew T.
Abstract: Platelet lifespan is regulated by intrinsic apoptosis. Platelet apoptosis can be triggered by BH3 mimetics that inhibit the pro-survival Bcl-2 family protein, Bcl-xL. Here, we investigated several small molecules that are reported to act as BH3 mimetics and compared their effects to the well-established BH3 mimetic, ABT-737. Platelet phosphatidylserine (PS) exposure was determined by flow cytometry. Changes in cytosolic Ca 2+ signaling were detected using Cal-520. Plasma membrane integrity was determined by calcein leakage. The roles of caspases and calpain in these processes were determined using Q-VD-OPh and calpeptin, respectively. As previously reported, ABT-737 triggered PS exposure in a caspase-dependent manner and calcein loss in a caspase and calpain-dependent manner. In contrast, AT-101 and sabutoclax triggered PS exposure independently of caspases. HA14-1 also triggered PS exposure in a caspase-independent but calpain-dependent manner. There were also significant differences in the pattern and protease-dependency of cytosolic Ca 2+ signaling in response to these drugs compared to ABT-737. Since there are clear differences between the action of ABT-737 and the other putative BH3 mimetics investigated here, AT-101, HA14-1 and sabutoclax cannot be considered as acting as BH3 mimetics in platelets. Furthermore, the platelet death caused by these drugs is likely to be distinct from apoptosis.